Higher comorbidity burden is associated with lower self-reported quality of life after stroke - Heinze, Marlene; Lebherz, Lisa; Rimmele, David Leander; Frese, Marc; Jensen, Märit; Barow, Ewgenia; Lettow, Iris; Kriston, Levente; Gerloff, Christian; Härter, Martin; Thomalla, Götz (Frontiers in Neurology, 2022)
Introduction This study assesses the association of comorbidity burden and polypharmacy with self-reported quality of life after stroke. Patients and methods We performed a post-hoc analysis of a prospective, single-center, observational study of outcome evaluation by patient-reported outcome measures in stroke clinical practice. Consecutive patients with acute ischemic stroke (AIS) were enrolled and self-reported health–related quality of life (HrQoL) was assessed 90 days after acute stroke using the Patient-reported Outcomes Measurement Information System 10-Question Short-Form (PROMIS-10). Comorbidities at baseline were assessed by the Charlson Comorbidity Index (CCI). Polypharmacy was defined as medication intake of ≥5 at baseline. We used linear regression analysis to study the association of CCI, polypharmacy and other clinical covariates with HrQoL after stroke. Results Of 781 patients (median age 76 years, 48.4% female) enrolled, 30.2% had a CCI Score ≥2, and 31.5% presented with polypharmacy. At follow up, 71 (9.1%) had died. In 409 (52.4%) reached for outcome evaluation, Global Physical Health T-Score was 43.8 ± 10 and Global Mental Health T-Score was 43.5 ± 8.76, indicating lower HrQoL than the average population. A CCI Score ≥2, higher NIHSS Score, female sex, dependency on others for dressing, toileting and mobility before index stroke, atrial fibrillation and hypertension were independent predictors of worse physical and mental health outcomes, while polypharmacy was not. Conclusion In patients with AIS, high comorbidity burden and polypharmacy are frequent. Comorbidity burden at admission is independently associated with worse self-reported physical and mental health three months after stroke.